Capital structure practices of the selected pharmaceutical companies in india. - V, MOHANRAJ; N, DEEPA (Journal of Management and Science, 2012)
The objective of this paper is to examine the capital structure practices of the selected pharmaceutical companies in India during 1991-92 to 2009-10. The econometric analysis shows that variables like Profitability, Size, Tangibility, Growth, Risk and Non-debt tax shield are the important determinants of capital structure of the selected pharmaceutical companies in India. The results indicate that most of the determinants of capital structure suggested by capital structure theories appear to be relevant for pharmaceutical firms. In this paper, Debt Equity Ratio has been used as the proxy for capital structure.